A health education programme to enhance the knowledge and communication skills of health care workers who serve people living with HIV / AIDS on HAART in Namibia - Chipare, Mwakanyadzenin Abigail; Dyk, Agnes van; Amukugo, Hans Justus (International Journal of Advanced Nursing Studies, 2015)
This paper aims at describing the findings of a health education programme that enhances the knowledge and communication skills of health-care workers who serve people living with HIV / AIDS on HAART in Namibia. Namibian health-care workers are unable to provide quality health care services to people who are living with HIV / AIDS (PLWHA) when they do not have the necessary knowledge, as well as adequate interpersonal communication and counselling skills. In a health care facility system, all patients either come from the community, or are referred from the wards or other departments by health-care workers. The health care worker as a sender conveys information (messages), and a patient (receiver) is expected to comprehend these messages and to respond by giving feedback to the sender who, in turn, provides feedback until the communication process is completed. The process should take place in a conducive environment without any interference, such as noise, to allow the swift completion of the communication process. The messages that both parties convey should be clear, accurate, coherent, and concise. This article covered the following: background, methods, ethical measures, results (participants’ responses) conclusions and recommendations.